Earnings Management antar Industri dan Faktor-Faktor Pembatasnya pada Perusahaan Publik di Bursa Efek Indonesia - Tatang A. Gumanti; Marmono Singgih (Jurnal Akuntansi dan Bisnis, 2006)
The purposes of this study are twofold, first, it examines differences in the level of earnings management at industrial level. Secondly, it examines the factors affecting earnings management of companies in the manufacturing sector listed at the Jakarta Stock Exchange. A sample of 109 companies with financial years of 2001 and 2002 were examined. Earnings management is proxied using discretionary accruals standardized by firm’s total assets. Leverage, company size, assets growth, sales change, and profitability were regressed over discretionary accruals. The findings reveal that there is no significant difference in the level of discretionary accruals among industry examined. Sales change and profitability both have positive and significant effect on discretionary accruals.